2012
DOI: 10.1590/s0037-86822012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enterotoxin-encoding genes and antimicrobial resistance in coagulase-negative and coagulase-positive Staphylococcus isolates from black pudding

Abstract: Introduction: Staphylococcal species are pathogens that are responsible for outbreaks of foodborne diseases. The aim of this study was to investigate the prevalence of enterotoxin-genes and the antimicrobial resistance profile in staphylococcus coagulase-negative (CoNS) and coagulasepositive (CoPS) isolates from black pudding in southern Brazil. Methods: Two hundred typical and atypical colonies from Baird-Parker agar were inoculated on mannitol salt agar. Eighty-two mannitol-positive staphylococci were submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Some studies have shown that CNS strains can harbor enterotoxins genes. Moura et al (2012) reported the presence of enterotoxins genes in CNS strains isolated from black pudding. The SE genes were also detected in coagulase negative staphylococci isolated from dairy products in Brazil (Rall et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that CNS strains can harbor enterotoxins genes. Moura et al (2012) reported the presence of enterotoxins genes in CNS strains isolated from black pudding. The SE genes were also detected in coagulase negative staphylococci isolated from dairy products in Brazil (Rall et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…DNA extractions and polymerase chain reaction (PCRs) for five classical staphylococcal enterotoxins genes (sea, seb, sec, sed and see) were performed as previously described by Moura et al 2012. The S. aureus ATCC 13565, ATCC 14458, ATCC 19095, ATCC 23235 and ATCC 27664 strains were used as positive controls for sea, seb, sec, sed and see genes, respectively.…”
Section: Detection Of Staphylococcal Enterotoxins Genesmentioning
confidence: 99%
“…Extraction of DNA and PCR assays - Genomic DNA was extracted following the standard method of phenol (Invitrogen) extraction and ethanol (Pro Analysis) precipitation (Sambrook & Russell 2001) with minor modifications, as previously described (Moura et al 2012). Plasmid DNA was extracted using standard miniprep methods (Sambrook & Russell 2001).…”
Section: Methodsmentioning
confidence: 99%
“…It is considered an opportunistic bacterium that shows its pathogenic ability in patients with immunocompromised patients, chronic diseases and long-term patients in hospital (Jean-Baptiste et al, 2011), as it enters the bloodstream and causes injuries to the circulatory system, especially in cases associated with the use of some medical devices, such as catheter tubes and blood implants, for hospitalized patients (Al-Mazroea, 2009). It is considered one of the most important bacterial species that cause hospital-acquired infections (Nosocomial Infections), as it is characterized by its ability to grow in thermal ranges from 15-43 • C (Moura et al, 2012;Götz et al, 2006). It has a NaCl tolerance of 15% and is resistant to the minimum inhibitory concentrations of some common antiseptics as well as its multiple resistance to antibiotics.…”
Section: Coagulase-negative Staphylococcimentioning
confidence: 99%
“…They grow naturally in many culture media. Staphylococci are classi ied depending on the production of coagulase coagulation (coagulase) into two main groups (Coagulase, that is, able to produce coagulation enzyme for blood plasma and the second group negative enzyme staphylococcus coagulase which is unable to produce coagulation enzyme for blood plasma (Moura et al, 2012).…”
Section: Introductionmentioning
confidence: 99%